Targeted Enrollment in Russian Universities: Current State, Problems and Solutions - Yu. S. Ezrokh (Moscow Polytechnic University, 2022)
Targeted studying in higher educational institutions is a system of training highly qualified personnel at the expense of the budget, with compulsory work at state enterprises, civil service, etc. Within its framework, a targeted (specially quota-based) enrollment of applicants studying at the state expense is carried out. The scientific and applied problem of this study is the insufficient efficiency of the state's use of the instrument of targeted education in higher education.The goal is to form a set of scientifically grounded proposals to improve the efficiency of using the targeted education system in Russia based on the systematic analysis of the practice of targeted enrollment system functioning at the present stage.The empirical base of the study included the results of the admission campaign in 2021 of the TOP-100 of the leading universities in Russia (according to Forbes magazine). The objects of observation were individual IT and medical areas of training.Results and scientific novelty: on the basis of a systemic analysis, the current state of the targeted education system in domestic universities is comprehensively described, on the basis of which the key problems of its functioning at the present stage are formulated: 1) in most cases, a significantly lower level of educational potential of target students in comparison with ordinary "budget" students; 2) the lack of opportunity for universities to influence the quality of applicants within the target quota; 3) proactive nature of the formation of directions for targeted training; 4) the absence in the public domain of formal criteria that are being used for selecting target areas (in most cases); 5) non-objective criteria for selecting potential target students; 6) constraining the choice of an educational institution by target students; 7) insufficient interest of employing enterprises to the implementation of the selection program of potential target groups; 8) lack of means of control and influence on the learning outcomes on the part of future employers; 9) the lack of data-centricity in organizing the targeted training system functioning in Russia. To overcome them, the article provides recommendations grouped into 4 blocks: 1) increasing the transparency of the system for selecting potential candidates for targeted training; 2) increasing the attractiveness of the target recruitment, entailing an increase in the educational potential of target applicants; 3) improving the quality of training target students; 4) control and strategic development of the targeted enrollment system in Russia.